Valorization of Food Processing Cake Waste into Organic Fertilizer Using a Double-Molasses Biofermentation System - Dwi Rizaldi Hatmoko; Agustin Patmaningrum; Ragil Retno Palupi; Andika Rahmawan; Rahmadi (Journal of Economics and Social Sciences (JESS), 2026)
The increasing generation of agro-industrial food processing waste presents environmental challenges while offering opportunities for resource recovery within a circular bioeconomy. This study evaluated the conversion of food processing cake waste from PT Belfoods Indonesia (Nganjuk, Indonesia) into organic fertilizer using a double-molasses biofermentation system with beneficial microorganisms activated by fresh sugarcane juice and palm sugar. A longitudinal experimental approach was applied through three stages: raw material characterization, biofermentation, and mature fertilizer production. Physicochemical properties were analyzed using standardized laboratory methods, while fertilizer performance was assessed through a 14-day field bioassay. Biofermentation significantly improved fertilizer quality, increasing total nitrogen from 0.17% to 0.69% and available phosphorus (P₂O₅) from 60.47 mg kg⁻¹ to 5,264.77 mg kg⁻¹. The final product contained no detectable hazardous heavy metals, including arsenic, cadmium, mercury, lead, and tin, confirming its environmental safety. Field observations showed improved plant growth, characterized by darker green leaves, greater foliage density, and stronger stems after fertilizer application. These findings demonstrate that the proposed double-molasses biofermentation system effectively transforms food processing cake waste into a safe, nutrient-enriched organic fertilizer with promising agronomic potential, supporting sustainable waste valorization and circular agricultural production.